Notes on Prosopocoilus Hope (Coleoptera: Scarabaeoidea: Lucanidae) from China, with the description of two new species - Huang, Hao; Chen, Chang-Chin (Zootaxa, 2011)
Prosopocoilus yangi Fukinuki has been rediscovered from central China and is redescribed with male and female genitalia illustrated. A similar species, P. simianshanus new species, is described from Chongqing, central China. Prosopocoilus reni new species is described from Hainan, China. Taxonomic notes are given for Kirchnerius guangxii Schenk, Prosopocoilus astacoides (Hope) and Prosopocoilus duplodentatus Benesh. Three new synonyms are presented: Prosopocoilus Hope = Kirchnerius Schenk new synonym; Prosopocoilus cyclommatoides Lacroix = Kirchnerius guangxii Schenk new synonym; Prosopocoilus oweni melli Kriesche = Prosopocoilus duplodentatus Benesh new synonym.